2021
DOI: 10.52633/jemi.v3i2.78
|View full text |Cite
|
Sign up to set email alerts
|

Linking Entrepreneurial Orientation and Innovation Intensity: Moderating Role of Environmental Turbulence

Abstract: This research aims to investigate the impact of entrepreneurial orientation dimensions on a firm’s innovation intensity along with the moderation of environmental turbulence. The dimensions of entrepreneurial orientation include autonomy, pro-activeness, risk attitude, innovation readiness and competitive aggressiveness, hence the study includes five direct hypotheses and five moderated hypotheses. The data was gathered through an online questionnaire. The sample size of the study was 386 small and medium ente… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 95 publications
0
3
0
Order By: Relevance
“…Matsuno et al (2002) found that EO positively affects firm performance combined with MO. However, a recent meta-analysis (Lopes et al, 2021) Zhou et al (2005) concluded that EO positively affects breakthrough innovations; in the same line, Zaidi and Zaidi (2021) found that EO significantly affects innovation intensity. However, the literature on OE has not differentiated between "new to the company" and "new to the world" innovations.…”
Section: Market Orientation and Innovationmentioning
confidence: 99%
“…Matsuno et al (2002) found that EO positively affects firm performance combined with MO. However, a recent meta-analysis (Lopes et al, 2021) Zhou et al (2005) concluded that EO positively affects breakthrough innovations; in the same line, Zaidi and Zaidi (2021) found that EO significantly affects innovation intensity. However, the literature on OE has not differentiated between "new to the company" and "new to the world" innovations.…”
Section: Market Orientation and Innovationmentioning
confidence: 99%
“…Results of this study highlight that EO helps small firms successfully reach their intended performance, where innovativeness and proactiveness have an especially important role in this process (Gupta & Batra, 2016;Putniņš & Sauka, 2020;Moric Milovanovic et al, 2021). Moreover, the positive moderating effect of environmental turbulence on EO -performance relationship shows that investing in EO-related strategies in uncertain environments brings affirmative effects to the firms' overall performance (Zaidi & Zaidi, 2021;Hina et al, 2021). Thus, firms should pay particular attention to the changes in their environment, i.e., to invest in environmental scanning activities, set up risk controls emerging from potentially too high levels of EO, focus on and engage in an only limited number of opportunities, as not to waste or deplete their limited and scarce resources (Wales et al, 2021).…”
Section: Implications For Managementmentioning
confidence: 98%
“…Besides the exhaustive literature on the EOperformance relationship, there is a substantial body of knowledge focused on examining the role of environmental turbulence in this relationship (Engelen, Kube, Schmidt, & Flatten, 2014;Zarei & Shaabani, 2016;Wang et al, 2020). Most scholars observed moderating (Balodi, 2019;Zaidi & Zaidi, 2021;Hina, Hassan, Parveen, & Arooj, 2021) and mediating (Vij & Bedi, 2012;Abiodun & Rosli, 2014) effects environmental turbulence has on the relationship between EO and firm performance. However, some fewer scholars tested the possible nonlinearities of these effects.…”
mentioning
confidence: 99%
“…Their results imply that EO is highly influenced by the top-management team and its characteristics. In addition to internal factors, many scholars (Hina et al 2021;Zaidi and Zaidi 2021;Wang et al 2020;Zahra 1991) have found that EO is also influenced by external factors such as environmental dynamisms, hostility, and heterogeneity.…”
Section: Entrepreneurial Orientationmentioning
confidence: 99%